Women’s Perceptions and Uses of Information and Communication Technologies in Nigeria and China: A Comparative Analysis - Ojokoh, Bolanle; Zhang, Ming; ., Samuel Oluwadare; .Akintola, Kolawole (Information Management and Business Review, 2013)
Nigeria and China were probably experiencing roughly similar economic fortunes only about two decades ago. Then, both had large populations and very low per capita incomes. But their socio-economic fortunes and growth rates have diverged dramatically since, with China now being a superpower and the second largest economy in the world, while Nigeria is still tottering along as one of the poorest countries in the world in terms of various global human development indices and rankings. The rapid economic transformations that China has experienced should normally be expected to be accompanied by equally dramatic socio-cultural changes, including the emancipation and greater participation of women in national economic activities. This study sought to investigate the extent to which women in China participate now in the ICT sector of their country compared to women in Nigeria. Data were collected through a questionnaire administered to cross sections of 123 and 151 women surveyed in purposively selected cities in Nigeria and China respectively. Women in both countries recognize the importance of ICT, but those in Nigeria were constrained from full utilization of ICT benefits due to electricity supply problems, financial constraints and inadequate training for ICT. The study found that improved levels of education of women promote the adoption and use of ICT by women in both countries, and that owning personal computers and the availability of time for women helped to increase participation of women in ICT. Some recommendations were made based on the findings.